The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1523/jneurosci.21-11-04081.2001
|View full text |Cite
|
Sign up to set email alerts
|

A Mechanism for Savings in the Cerebellum

Abstract: The phenomenon of savings (the ability to relearn faster than the first time) is a familiar property of many learning systems. The utility of savings makes its underlying mechanisms of special interest. We used a combination of computer simulations and reversible lesions to investigate mechanisms of savings that operate in the cerebellum during eyelid conditioning, a well characterized form of motor learning. The results suggest that a site of plasticity outside the cerebellar cortex (possibly in the cerebella… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
220
3
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 211 publications
(250 citation statements)
references
References 55 publications
(115 reference statements)
26
220
3
1
Order By: Relevance
“…Consistent with previous studies, we observed no SLRs before training (Fig. 6 B, T1) (Medina et al, 2001;Ohyama et al, 2003). Five sessions of unpaired training failed to promote learning and, importantly, also failed to support the acquisition of SLRs (Fig.…”
Section: Experiments 5: Slrs Are Learned and Associativesupporting
confidence: 92%
See 4 more Smart Citations
“…Consistent with previous studies, we observed no SLRs before training (Fig. 6 B, T1) (Medina et al, 2001;Ohyama et al, 2003). Five sessions of unpaired training failed to promote learning and, importantly, also failed to support the acquisition of SLRs (Fig.…”
Section: Experiments 5: Slrs Are Learned and Associativesupporting
confidence: 92%
“…First, infusing picrotoxin into the AIN at different time points during initial acquisition reveals that the probability of observing SLRs parallels that of normal conditioned responses, consistent with the notion that plasticity induction in the AIN is the rate limiting factor in acquisition (Medina et al, 2001). Second, the observation of initial learning in the cerebellar cortex that is later revealed by inducing AIN plasticity suggests that AIN plasticity is necessary for the expression of conditioned responses and requires initial plasticity in the cerebellar cortex for its induction (Ohyama and Mauk, 2001).…”
Section: Functional Contributions Of Plasticity In the Ainsupporting
confidence: 67%
See 3 more Smart Citations